2006
DOI: 10.1021/jp0634959
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Nitrogen Atoms with Methyl Radicals:  Are Spin-Forbidden Channels Important?

Abstract: A computational study of the N(4S) + CH3 reaction has been carried out. The reactants approach through an attractive potential surface leading to an intermediate, H3CN, whose formation does not involve any barrier. In agreement with the experimental results, the dominant channel for this reaction is H2CN+H. The theoretically estimated rate coefficient for the overall process at 298 K is 9.1 x 10(-12) cm3 s(-1) molecule(-1), which is nearly 1 order of magnitude lower than the experimental result, but also much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
5
18
0
Order By: Relevance
“…These authors suggest that HCN formation is associated with H 2 , however HCN + H 2 production is spinforbidden and needs intersystem crossing to occur. Additionally recent ab-initio calculations (Cimas & Largo 2006) found almost 100% of H 2 CN production in good agreement with previous calculations (Nguyen et al 1996). As H 2 CN may have enough internal energy (153 kJ mol −1 ) to overcome the dissociation barrier for C-H dissociation (130 kJ mol −1 ), some HCN + H + H may be produced (Nguyen et al 1996).…”
Section: Discussionsupporting
confidence: 86%
“…These authors suggest that HCN formation is associated with H 2 , however HCN + H 2 production is spinforbidden and needs intersystem crossing to occur. Additionally recent ab-initio calculations (Cimas & Largo 2006) found almost 100% of H 2 CN production in good agreement with previous calculations (Nguyen et al 1996). As H 2 CN may have enough internal energy (153 kJ mol −1 ) to overcome the dissociation barrier for C-H dissociation (130 kJ mol −1 ), some HCN + H + H may be produced (Nguyen et al 1996).…”
Section: Discussionsupporting
confidence: 86%
“…However, the (HCN + H 2 ) production is spinforbidden and needs an intersystem crossing process to occur. Additionally, recent ab initio calculations (Cimas & Largo 2006) found almost 100% of H 2 CN production, in good agreement with previous calculations (Nguyen et al 1996). As H 2 CN may have enough internal energy to overcome the dissociation barrier for C-H dissociation, some (HCN + H + H) may be produced (Nguyen et al 1996).…”
Section: (±25%)supporting
confidence: 88%
“…A computational study of the CH 3 + N − −→ products reaction shows a preference for the CH 3 + 4 N − −→ H 2 CN + H pathway 64 . This study finds the CH 3 + 2 N − −→ HCN + H 2 channel to be negligible.…”
Section: Case Study 2: 2 H2cn −−→ Hcn + H2cnhmentioning
confidence: 99%
“…In this case study, we analyze the three suggested main branches for CH 3 + N − −→ products using CVT (see the methods section for full details). Computational studies show that CH 3 + 4 N − −→ products reactions first proceed through a barrierless reaction to H 3 CN on the triplet surface 64,143 . We confirm this barrierless reaction (CH 3 + 4 N − −→ 3 H 3 CN) and calculate its rate coefficients at the BHandHLYP/aug-cc-pVDZ level of theory to be 3.3×10 −11 cm 3 s −1 .…”
Section: Case Study 2: 2 H2cn −−→ Hcn + H2cnhmentioning
confidence: 99%